Pliocene Mollusca (Bivalvia, Gastropoda) from the Sørsdal Formation, Marine Plain, Vestfold Hills, East Antarctica: taxonomy and implications for Antarctic Pliocene palaeoenvironments. Issue 4 (1st October 2016) - Quilty, Patrick G.; Darragh, Thomas A.; Gallagher, Stephen J.; Harding, Lucy A.
Abstract : Quilty, P.G., Darragh, T.A., Gallagher, S.J. & Harding, L.A. July 2016. Pliocene Mollusca (Bivalvia, Gastropoda) from the Sørsdal Formation, Marine Plain, Vestfold Hills, East Antarctica: taxonomy and implications for Antarctic Pliocene palaeoenvironments. Alcheringa 40, XXX–XXX. ISSN 0311-5518. Pliocene shallow-water marine sediments at Marine Plain (centred on 68°37.7ʹS; 78°07.8ʹE) and covering approximately 10 km² in the Vestfold Hills, East Antarctica, have yielded six species of gastropods, and 11 species of bivalves from two beds within the Sørsdal Formation. Most of the material is close to in situ but some specimens have been disturbed from their life position; there is no evidence of significant transport. The gastropods include Nacella concinna (Strebel, 1908), Falsimargarita parvispira Quilty, Darragh, Gallagher & Harding sp. nov., indeterminate species of trochids and naticids, Chlanidota ( Chlanidota ) sp. cf. C. signeyana Powell, 1951, and two species of Trophon/Trophonella . Bivalves include Ennucula sp. aff. E. grayi (d'Orbigny, 1846), Aequiyoldia defossata Quilty, Darragh, Gallagher & Harding, sp. nov., ' Pectunculina ' sp., Lissarca sp., Austrochlamys anderssoni (Hennig, 1911), Ruthipecten campestris Quilty, Darragh, Gallagher & Harding sp. nov., Adamussium necopinatum Quilty, Darragh, Gallagher & Harding sp. nov., Limatula ( Antarctolima ) sp. cf. L. hodgsoni (Smith, 1907), Cyclocardia magna Quilty, Darragh, Gallagher & Harding sp. nov., ? Hiatella sp. cf. H. arctica (Linnaeus, 1767) and Laternula elliptica (King, 1832). Preservation varies considerably owing to recrystallization, dissolution or distortion through compaction, so several species are left in open nomenclature. Oxygen isotope data indicate that water temperature was 4–7.5°C at the time of shell growth. Many species or species groups are now extinct or have migrated away from the Antarctic to the sub-Antarctic region. An Antarctic mollusc fauna has been characteristic of the region for much of the Cenozoic. Patrick G. Quilty [ p.quilty@utas.edu.au ], Discipline of Earth Sciences, University of Tasmania, Private Bag 79, Hobart, Tasmania 7001, Australia; Thomas A. Darragh [ tdarragh@museum.vic.gov.au ], Museum Victoria, GPO Box 666 Melbourne, Victoria 3000, Australia; Stephen J. Gallagher [ sjgall@unimelb.edu.au ], School of Earth Sciences, The University of Melbourne, Victoria 3010, Australia; Lucy A. Harding [ harding.lucy.a@edumail.vic.gov.au ], School of Earth Sciences, The University of Melbourne, Victoria 3010, Australia.